The Visual Learning Style In the Thematic Learning Process at grade V SDN 12 Kampung Durian, Padang Timur District, Padang - Dini Putri Arifah, Nabila; Osman, An-Nisa; Putri, Liza Amanda (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2023)
This study aims to analyze how visual learning styles in the thematic learning process in class V at SDN 12 Kampung durian, East Padang District, Padang City. This study uses a qualitative approach with a descriptive type. The subjects of this research are fifth grade teachers and students. This research was conducted at SDN 12 Kampung durian, East Padang District, Padang City in July 2022. The data collection techniques used were observation, interviews and documentation. The results showed that the application of visual learning styles in the thematic learning process, students were more likely to have a visual learning style in which students preferred to be read to rather than read alone. Teachers have an important role in increasing the interest of students, namely by trying to make various methods, media that are in accordance with thematic learning in the classroom. The most prominent learning style used by students is the visual learning style. This is because students prefer to learn by watching the teacher explain in front and also students prefer to read accompanied by related pictures from reading or learning materials